Optimizing observer performance of clinic blood Pressure measurement: a position statement from the Lancet Commission on Hypertension Group [Otimização do desempenho do observador na medição clínica da pressão arterial: posicionamento do Grupo da Lancet Commission on Hypertension] - Padwal, R; Campbell, NRC; Schutte, AE; Olsen, MH; Delles, C; Etyang, A; Cruickshank, JK; Etyong, A; Stergiou, G; Rakotz, MK; Wozniak, G; Jaffe, MG; et al. (Pan American Health Organization, 2020)
High blood pressure (BP) is a highly prevalent modifiable cause of cardiovascular disease, stroke, and death. Accurate BP measurement is critical, given that a 5-mmHg measurement error may lead to incorrect hypertension status classification in 84 million individuals worldwide. This position statement summarizes procedures for optimizing observer performance in clinic BP measurement, with special attention given to low-tomiddle- income settings, where resource limitations, heavy workloads, time constraints, and lack of electrical power make measurement more challenging. Many measurement errors can be minimized by appropriate patient preparation and standardized techniques. Validated semi-automated/automated upper arm cuff devices should be used instead of auscultation to simplify measurement and prevent observer error. Task sharing, creating a dedicated measurement workstation, and using semi-automated or solar-charged devices may help. Ensuring observer training, and periodic re-training, is critical. Low-cost, easily accessible certification programs should be considered to facilitate best BP measurement practice.